The Core Application of Energy-saving Technology for HVAC Systems in High-rise Buildings - Huawei, Zhang (IOP conference series. Materials Science and Engineering, 2019)
Air conditioners were originally high-energy-consuming appliances. The introduction of energy-saving technologies in air-conditioning systems will help achieve energy-saving and emission-reduction goals. At present, the energy-saving technology of HVAC systems has been widely used in the installation and construction of high-rise building electrical appliances, and has achieved good results. This paper will briefly introduce the function and characteristics of HVAC, systematically discuss the energy-saving problems of HVAC systems in high-rise buildings, and discuss the application schemes of energy-saving technologies for HVAC systems in high-rise buildings.